ANALISIS POTENSI KEBANGKRUTAN KOPERASI DI KABUPATEN PANGKEP - Samsu Gaffar (Economos : Jurnal Ekonomi dan Bisnis, 2022)
The bankruptcy of a cooperative is a business condition that is not desired by all cooperative stakeholders. The bankruptcy of a cooperative is sometimes not only miserable for its members as owners and customers, but not a few bankruptcies of cooperatives leave a prolonged problem. This study aims to determine the potential for bankruptcy for cooperatives in Pangkep Regency using the Altman Z-Score formula. The research data is sourced from the financial statements of Cooperatives taken by purposive sampling, namely cooperatives that have held the Annual Member Meetings and submitted financial reports for the 2020 Fiscal Year. The results of this study indicate that of the 20 selected samples of cooperatives, 19 cooperativesare classified as healthy with a Zi value range. 3.88-9.59, and there is 1 cooperative classified as prone to bankruptcy with a Zi value of 1.25. It can be concluded that generally Cooperatives in Pangkep Regency are still healthy in 2020. For cooperatives that are categorized as prone to bankruptcy, it is important to immediately increase their working capital so that they do not experience bankruptcy